DETECTION OF FICTITIOUS COMPANIES BY PRIMARY FINANCIAL MONITORING ENTITIES - Kryshtal, Halyna (Current Problems of Sustainable Development, 2026)
National risk criteria that may indicate the establishment of business relationships with a shell company have been examined, along with international best practices for identifying legal entities with signs of fictitious activity. An extended analysis of the geographic risk criterion was conducted, taking into account the requirements of Ukrainian and European regulatory acts regarding the use of risk indicators by reporting entities in the field of financial monitoring based on the location and registration of clients, beneficial owners, and counterparties. Discrepancies were identified between the approaches of Ukraine and the European Union regarding the use of registration risk criteria for cooperation with shell companies. In particular, EU reporting entities are required to evaluate not only the client’s country of registration but also the links between the legal entity, its clients, or owners and high-risk jurisdictions or offshore states. Furthermore, international recommendations emphasize the importance of assessing official and unofficial nominee shareholders and directors of the client, analyzing its credit transactions, and the potential involvement of the company in trade-based money laundering schemes. The characteristics of companies that conduct economic activity but are utilized in money laundering schemes have been categorized. The features of ‘shelf companies,’ which may be used for money laundering after their sale to criminal elements, were analyzed. The study emphasizes the importance of reporting entities creating their own tools for detecting fictitious companies by utilizing internal sources of information on actual client transactions and data obtained from specialized data aggregators. Internal tools for identifying shell companies should be aimed at detecting anomalous activity of legal entities through the analysis of cash flows, the presence of assets and personnel, the detail of supporting documentation, the profitability of operations, and the presence of a ‘digital footprint.’ External tools should focus on analyzing information from public state registries and combining the obtained data with information about other legal entities and their controllers.